Sulfur Isotope Constraints on the Petrogenesis of the Kimberley Kimberlites. (23rd November 2021) - Fitzpayne, Angus; Giuliani, Andrea; Magalhães, Nivea; Soltys, Ashton; Fiorentini, Marco L.; Farquhar, James
Abstract: Cretaceous kimberlites in southern Africa have been suggested to host deeply subducted material in their mantle sources based on radiogenic isotope systematics. However, potential subducted material contributions to the volatile budget, including sulfur, of these kimberlites is unclear. Here we report new petrographic, geochemical, and isotopic data on sulfides and sulfates in sub‐volcanic kimberlites from Kimberley, South Africa. The examined kimberlites were divided into four groups based on their sulfide mineralogy, sulfur contents, and isotopic compositions. None of these groups exhibit clear signs of mass‐independent fractionation. Three samples contain sphalerite, have moderate bulk‐sulfide S concentrations (203–329 μg/g) and highly negative bulk‐sulfide δ 34 S values (−10 to −13‰). Four samples have moderate‐to‐high bulk‐sulfide S contents (220–745 μg/g), positive δ 34 Ssulfide values (+0.2 to +14‰), and contain galena, pyrite or secondary Cu‐sulfides as the dominant sulfides. These groups of S‐rich kimberlites were probably contaminated by fluids sourced from local country rocks. The remaining eight samples contain negligible amounts of crustal sulfides (e.g., sphalerite, galena), have lower bulk‐sulfide S concentrations (≤111 μg/g), and display a different δ 34 Ssulfide range (−5.7 to +1.1‰) compared to the S‐rich groups. By considering only the five samples with fresh primary Cu‐Fe‐Ni sulfides, the δ 34 S range contracts to between −5.7 and −3.4‰, which is considered representative of the mantle source composition. This range indicates the presence of a deeply recycled sedimentary component in the melt source. The combination of detailed sulfide petrography and S isotope geochemistry in fresh kimberlite rocks provides a further tool to investigate mantle chemical geodynamics through time. Key Points: S isotopic compositions of fresh, uncontaminated Kimberley kimberlite rocks require a contribution from deeply recycled sedimentary material Combining sulfide petrography and S isotope geochemistry elucidates occurrence and origin of deeply subducted volatiles in kimberlite source